Implementasi Metode Extreme Programming Terhadap Line-Up Produk Handphone pada PT. Smartfren Telecom - Sahlan; Maulana Muhamad Sulaiman; Andi (CV. Multi Kreasi Media, 2026)
Warehousing is a component of a company's logistics system responsible for storing products and providing management with information regarding the status, condition, and movement of stored goods. Currently, PT Smartfren Telecom's warehousing system faces several challenges, notably discrepancies between physical stock levels and warehouse records. Consequently, there is a need for an application that enables data integration, stores both historical and current data, and improves the efficiency of warehousing administration and documentation processes. This final project involves a system analysis to identify requirements, followed by the design of a warehouse information system application. The system design employs an object-oriented approach, utilizing the Unified Modeling Language (UML) and the Extreme Programming methodology. The database design utilizes a Relational Database Management System (RDBMS) approach—requiring a transition from the object-oriented model to a relational one—followed by the design of the user interface. The resulting warehouse information system design generates inputs and outputs that enhance warehouse operations. Application validation results indicate that the tested functions are valid and operate correctly.